O atendimento às necessidades decorrentes do uso de drogas dos adolescentes em conflito com a lei: uma análise da atenção psicossocial das casas de semiliberdade no Paraná. - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2022)
Drug use is present in the reality of Brazilian youth, especially in the daily lives of adolescents in conflict with the law, which demands reflections on Socio-educational Care and its interface with the Mental Health Policy. The objective of this research is to analyze psychosocial care in the face of the needs arising from the use of drugs presented by adolescents in compliance with a socio-educational measure of semi-freedom of the Houses of Semi freedom of the State of Paraná, especially in its relationship with the Psychosocial Care Network (RAPS) and its equipment implanted in the territory. The dissertation is the result of a qualitative and exploratory research. In the bibliographic phase, a literature review was carried out in the field of knowledge production on social public policies, Socio-educational Care, Brazilian Psychiatric Reform, RAPS, psychosocial care, adolescents in conflict with the law and drug use. With regard to methodology, the research was conducted in the light of the theoretical framework of Marxist and Gramscian authors and the method adopted is historical-dialectical materialism. The understanding of adolescence as a peculiar phase of human development is based on the bioecological model and main concepts proposed by Urie Bronfenbrenner. For data collection, a semi-structured interview was conducted with the professionals who make up the technical teams of the Houses of Semiliberdade of the State of Paraná. A data form was also applied on the professional information of the research participants. The content analysis technique was used in the data analysis technique. The results indicate that the logic of psychosocial care is hegemonic as a proposal to address issues related to mental health and the needs arising from the use of drugs by professionals of casas de Semiliberdade; the most activated RAPS equipment is the CAPS, demonstrating to be the strongest link in the network with regard to referrals raised in the research problem; the strengthening of social policies and the articulation with the network are essential in the implementation of the socio-educational measure of semiliberdade, but it is verified that the neoliberal advance and the conservative tendency accentuates the weakness of social policies. With the so-called New Mental Health Policy, there are setbacks such as the definancing of equipment in the territory redesigning the RAPS and precariousing psychosocial care. This process advances as raps incorporate the third sector, the so called Therapeutic Communities and the beds in psychiatric hospitals. It is observed that the regressive movement around drug policies in Brazil and the intensification of the criminal state bring up old dilemmas not overcome in socio-educational care, reinforcing the impasses around protective and punitive aspects. The research aims to collaborate for the knowledge of this specific reality of care within the scope of Socio-educational Care in Paraná, as well as the improvement of socio-education and its affirmation as public policy.
Keywords: Atenção psicossocial; Atendimento socioeducativo; Adolescente em conflito com a lei; Uso de drogas; Psychosocial care; Socio-educational care; Adolescent in conflict with the law; Drug use; CNPQ::CIENCIAS SOCIAIS APLICADAS